Hyperbranched bisphosphinoamine ligands: synthesis, characterization and application in ethylene oligomerization. Issue 15 (3rd August 2017) - Wang, Jun; Zhang, Na; Shi, Weiguang; Shang, Yiteng; Li, Cuiqin
Abstract: Two hyperbranched bisphosphinoamine (PNP) ligands and chromium complexes were synthesized in good yield with 1.0 generation (1.0 G) hyperbranched macromolecules, chlorodiphenylphosphine (Ph2 PCl) and CrCl3 (THF)3 as raw materials. The hyperbranched PNP ligands and chromium complexes were characterized by FT-IR, 1 H NMR, 31 P NMR, UV and ESI-MS. Comparing with the chromium complexes, the hyperbranched PNP ligands, in combination with Cr(III), and activation by methylaluminoxane (MAO) in situ generated species with better catalytic performance for ethylene oligomerization. The effect of solvent, chromium source, ligand/Cr molar ratio, reaction temperature, Al/Cr molar ratio and reaction pressure on the catalytic activity and product selectivity were studied. The results showed that with increase of ligand/Cr molar ratio, reaction temperature and Al/Cr molar ratio, the catalytic activity increased at first and then decreased. However, the catalytic activity continuously increased with increase of reaction pressure. Under the optimized conditions, the catalytic system of hyperbranched PNP/Cr(III)/MAO led to catalytic activity of 2.68 × 10 5  g/(mol Cr·h) and 37.71% selectivity for C6 and C8 . Abstract :